Community Perceptions of Impacts of Ecotourism and Its Implications on Ecotourism Development in the Balikpapan Bay, East Kalimantan - Sayektiningsih, Tri Sayektiningsih; Ardiyanto, Ardiyanto Wahyu Nugroho; Ishak, Ishak Yassir; Ulfah , Ulfah Karmila Sari; Amir , Amir Ma'ruf; Mukhlisi , Mukhlisi Mukhlisi; Adi , Adi Surya; Suryanto , Suryanto Suryanto (Forestry Department, University of Muhammadiyah Makassar, 2019)
Understanding local community perceptions towards ecotourism is important since community has a crucial role in determining sustainable ecotourism. This research aimed to identify community perceptions towards impacts of ecotourism as well as to analyse the relationships between perception and ecotourism responsible behaviour. Other goal of this study was to analyse the relationship between ecotourism responsible behaviour and social factors. Data was collected in 4 villages adjacent to the Balikpapan bay, namely Maridan, Telemow, Binuang, and Mentawir. We used the quota technique to sample respondents. For each village, we took 40 respondents randomly. Data was then analysed using descriptive statistics, Spearman correlation, and Kruskal Wallis test. We found that community around the Balikpapan Bay thought that ecotourism was able to bring positive impacts for village and community. A Kruskal Wallis test revealed that there was no significant difference regarding perceptions among 4 villages. We found that there was a correlation between ecotourism responsible behaviour and gender. Implications of community’s perceptions to ecotourism development around the Balikpapan bay were then discussed.